PHYTOCHEMICAL AND ANTIOXIDANT ACTIVITY of MANGROVE PLANT Soneratia sp. - Mahmiah Mahmiah; Rina Andayani (UNEJ e-Proceeding)
At the moment, plants use as medicine are mostlyland plants, while plants derived from water such asmangroves have not received much attentions.Some of the mangrove plants that can be used asmedicine are Acanthus ilicifolius, Avicennia alba,Avicennia marina, Avicennia offinalis, Bruguieracylindrical, Bruguiera exaristata, Bruguieragymnorrhiza, Ceriops tagal, Hisbiscus tiliaceus,Ipomoea pes-capre, Lumnitzera racemosa, Nypafructicans, Pluchea indica Rhizophora apiculata,Soneratia sp., dan Sonneratia alba. The plants wereutilized as antiasma, antidiuretic, antidiabetic, itchrelieve, etc. Purnobasuki, 2004).One of the mangroves that are often found on theEast Coast of Surabaya, East Java is Soneratia sp ..which is classed as true mangrove flora.Ethnobotanically, the wood and stem are used astraditional medicine as pain reliever. Based onresearch conducted by Mahmiah (2012)studyingphytochemical aspect of Avicennia marina from eastcoast region of Surabaya,it was known that the stemand leaves of the plant contained phenoliccompounds.Taking into account the existence of the waves andextreme weather conditions in the East Coast regionof Surabaya, it was hypothesized that the secondarymetabolite compounds produced by the plantswould be different. Based on that hypothesis it wasnecessary to do a research on Soneratia sp. plantlocated on the East Coast of Surabaya with the aimof exploring the content of secondary metabolitesfrom the stem of the plant.Methods that were used to accomplish that aimwere (1) preliminary test; (2) phytochemicalscreening; (3) GC-MS analysis and (4) antioxidanttest